Historical Aspects of Printing and Publishing in Languages of the Middle East : Papers from the Symposium at the University of Leipzig, September 2008. - Roper, Geoffrey (Islamic manuscripts and books., 2013)
These essays deal with aspects of the development of printing and print culture, in the 10th-20th centuries, in Iran, Kurdistan, Turkey, Egypt, the Maghrib, Germany and Latin America, and in the Arabic, Judæo-Arabic, Syriac, Ottoman Turkish, Kurdish and Persian languages.